2017
DOI: 10.1007/s00268-017-3954-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment of Gastroesophageal Reflux Disease

Abstract: Medical treatment is effective in the majority of patients with gastroesophageal reflux disease (GERD). Lifestyle modifications are often recommended for patients with GERD, although the data supporting lifestyle recommendations are limited. Antacids are often used to treat the symptoms of GERD, but their effect is short-lived. H2-receptor antagonists and proton-pump inhibitors provide more effective options for remission of GERD symptoms and healing of esophagitis. Prokinetic medications (e.g., metoclopramide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 84 publications
0
7
0
1
Order By: Relevance
“…Moreover, in practice, the combination of magaldrate and alginate at bedtime may be useful for many patients with nonacid or mixed reflux according to MII‐pH. H 2 ‐receptor antagonists are second‐line treatment regarding the short duration of action (4‐8 hours) of these drugs 150 . In case of acid reflux, the prescription of twice‐daily PPIs could be associated with better symptom improvement than a once‐daily PPI prescription 151 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in practice, the combination of magaldrate and alginate at bedtime may be useful for many patients with nonacid or mixed reflux according to MII‐pH. H 2 ‐receptor antagonists are second‐line treatment regarding the short duration of action (4‐8 hours) of these drugs 150 . In case of acid reflux, the prescription of twice‐daily PPIs could be associated with better symptom improvement than a once‐daily PPI prescription 151 …”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was found between high RSI scores and excessive caffeine intake (r s = 0.322 [fair]; p = 0.043), indicating that participants with excessive caffeine intake had higher RSI scores. Although some studies have shown that caffeine intake may be related to reflux (Pehl et al, 1997), more recent literature has found this data weak (Katz et al, 2013;Kroch & Madanick, 2017). The relationship between caffeine and the RSI specifically has not been explored to the authors' knowledge.…”
Section: Comparisons With Other Studiesmentioning
confidence: 92%
“…Conservative measures, as already mentioned, include weight loss, if the patient is obese and overweight, the elevation of the bed head, avoiding late-night meals, and reducing the consumption of alcohol, fat, caffeine, and chocolate intake [ 3 , 5 ]. Medical treatment is commonly achieved through antacids, H2 receptor antagonists (H2RAs), and proton pump inhibitors for heartburn and acid regurgitation [ 28 ]. PPIs work by inhibiting the acid secretion from parietal cells.…”
Section: Reviewmentioning
confidence: 99%